2020
DOI: 10.1177/0163278720923224
|View full text |Cite
|
Sign up to set email alerts
|

Notes From the Field: Vape Shop Business Operations Compliance in the Wake of COVID-19

Abstract: The novel 2019 Coronavirus Disease pandemic has led to the closing of all but essential businesses in California. However, several nonessential businesses have remained open in Southern California despite the mandated "stay at home" order issued by the governor. As part of an ongoing vape shop project involving 88 participating shops, this study investigated the number of vape shops that remained open amidst the coronavirus outbreak and related mandates. Examination of shop social media websites and telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…This study adds to existing literature by further supporting the notion that the frequency of vape shop noncompliance within certain ethnic communities may be attributed to the lack of proper culturally sensitive messages and the quality of communication between public health officials and small businesses amid a pandemic which may lead to a misunderstanding of the state order (Medel et al, 2020). Pandemic-specific material from local and state authorities must be culturally and linguistically sensitive when disseminated to vulnerable, ethnic communities (such as Hispanic/ Latino and Korean/Asian communities).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This study adds to existing literature by further supporting the notion that the frequency of vape shop noncompliance within certain ethnic communities may be attributed to the lack of proper culturally sensitive messages and the quality of communication between public health officials and small businesses amid a pandemic which may lead to a misunderstanding of the state order (Medel et al, 2020). Pandemic-specific material from local and state authorities must be culturally and linguistically sensitive when disseminated to vulnerable, ethnic communities (such as Hispanic/ Latino and Korean/Asian communities).…”
Section: Discussionsupporting
confidence: 55%
“…The executive order allowed only essential business sectors to remain open, thus mandating sectors not listed as essential to close and comply with state regulations (California Resilience Roadmap, 2020). Previous evidence in Southern California indicated that in violation of state law, vape shops-a nonessential sector within California-remained open during the beginning of the pandemic (Berg et al, 2020;Medel et al, 2020;Winton & Hernandez, 2020). Because noncompliance with the state order could compromise public safety during COVID-19, it is critical to conduct periodic compliance assessments within nonessential businesses such as vape shops to verify adherence to both state and local policies over time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many retailers adapted to the pandemic by conducting business online, and many consumers now purchase goods online and use delivery services [ 31 ]. Although many state governors issued executive orders requiring the temporary closure of tobacco specialty shops during shelter-in-place periods, compliance with the mandated closures was low among some vape shops, with considerable variations across states and localities and by neighborhood demographics [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Little is known about whether vape shops complied with state-ordered temporary business closures. One study found that, in a sample of 88 vape shops in Southern California, 61.4% were open during California's first shelter-in-place period, 13 regardless of state orders mandating them to close. 14 Moreover, similar to tobacco companies, vape product manufacturers exploited the COVID-19 crisis in their marketing.…”
Section: Introductionmentioning
confidence: 99%